Pengujian Tahanan Isolasi Trafo Tegangan Di Gardu Induk Telukjambe Karawang - Samsul Bahri Siregar; Reni Rahmadewi (Universitas Islam Lamongan, 2021)
Electricity is a collection of components or electrical devices such as generators, transformers, transmission lines, distribution lines, and loads, which are connected and form a system. Maintenance is one of the most important things that must be considered in the operation of the electrical system. Voltage transformer is a device that transforms a higher system voltage to a lower system voltage for indicator equipment, measuring instruments, and relays. In this research, quantitatively, this is done by testing from the box panel on the voltage transformer and each coil has ameasuring limit, recording the test results is carried out at 60 seconds and there are 2 places, namely busbar 1 and busbar 2 and 6 measurements of insulation resistance on the transformer. voltage. This test is not on Phase R and Phase T because the equipment is being transferred to another substation. The results of the voltage insulation resistance test under normal and good conditions are above the minimum limit of insulation resistance and the voltage transformer is fully operational.